The outcome of macroprolactinomas resistant to dopamine agonists - Coculescu, M; Anghel, R; Trifanescu, R; Voicu, D; Karavitaki, N; Wass, J (2005)
Aim: The present study aims to assess the final outcome after combined therapeutic approaches in patients with macroprolactinoinas resistant to dopamine agonists (DA). Patients: Records of patients with macroprolactinoma hospitalized in the Institute of Endocrinology, Bucharest, between 1978-2005, were reviewed. There were 29 eligible patients resistant to DA therapy (8 men and 21 women), out of 119 patients with macroprolactinoinas; age at diagnosis ranged between 16-59 years. Methods: Rapid fluoroimmunoassay using Europium was used for hormonal levels; computed tomography imaging and/or MRI were used for tumor size. Study design: The resistance to DA drugs was evaluated using minimal criteria: the lack of prolactinoma response to current daily close of Bromocriptine (BRC) 7.5 mg/day or to Cabergoline (CAB) up to 2 mg/week for at least 6 months (step 1) or maximal criteria: the lack of response to high BRC doses (30 mg/day) or CAB doses between 2.5-4 mg/week for at least 6 months (step 2). The lack of response was considered if PRL levels remained above the upper normal limit (20 ng/mL) and the tumor mass size decreased with less than 50%. All resistant cases at step 1 received thereafter maximal medical therapy with DA drugs, according to step 2. Thereafter, resistant macroprolactinomas after step 2 were submitted to step 3 - high voltage radiotherapy ± surgery. Results: Outcome of medical therapy with DA (n=29): Overall, 7 resistant macroprolactinomas were solved by increasing BRC dose (n=5) or changing BRC to CAB (n=2). But 22/119 (18.5%) patients remained resistant to DA drugs independent of dose, duration or type of drug used. 14 patients failed to normalize PRL levels despite CAB treatment in doses up to 7 mg/week. Outcome of radiotherapy alone or combined with surgery (n=15): PRL normalization was achieved in 4 patients out of the only 7 assessed at least at 18 months after radiotherapy. Withdrawal of DA therapy revealed 2 cured cases, both after radiotherapy and surgery. Outcome of surgery: Only one patient normalized PRL levels after surgery, but she soon relapsed. Apparently, only one case of acquired resistance to DA drugs was revealed. Conclusion: The resistance was successfully over passed in 38% cases (11 out of 29). Adding these results to the low cure rate of DA responsive prolactinomas, proved by drug withdrawal, it is tempting to suggest that a selection of biological resistant cells is produced by the medical therapy in majority of macroprolactinomas**.